CHEMPHYLACTIC STUDIES WITH IVERMECTIN ON BOVINE NEMATODE INFECTION - JOHAL, MANJEET; KAUR, MANJEET (UTTAR PRADESH JOURNAL OF ZOOLOGY, 1995)
Twenty one calves were used to confirm efficacy of ivermectin given orally against naturally acquired gastrointestinal nematodes. The calves were divided into three groups: Group I, to which two doses of ivermectin, 0.15 mg/kg and 0.2 mg/kg were given orally; Group II, to which a single dose of 0.3 mg/kg bwt was given and Group III was used as control and kept unmedicated. Faecal examination revealed that ivermectin treated calves showed a marked decrease in faecal egg counts, whereas, no significant change took place in controls. Efficacy rfivermectin at 0.2 mg/kg was 100% against Strongyloidespapillosus and stronglyles whereas a dose rate of 0.3 mg/kg bwt was required to achieve 100% efficacy against Neoascaris vitulorum.